The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

Assessing Sea lice infection levels in Irish Atlantic salmon farms: Metrics and treatment trigger levels - Bela Klimesova; Katie O'Dwyer; Jack D'Arcy; Anita Talbot; Olga Lyashevska; Hamish Rodger; Catherine McManus; Neil M. Ruane (Aquaculture, 2026)

Comparing Genome Sequencing Methods to Reconstruct the Spread of Piscine Myocarditis Virus in Ireland - Andrew J. Tighe; Jens Carlsson; Neil M. Ruane (Journal of Fish Diseases, 2025)
Piscine myocarditis virus (PMCV), a double‐stranded RNA virus, is the causative agent of cardiomyopathy syndrome (CMS) in Atlantic salmon Salmo salar , which was first reported in Ireland in 2012. PMCV continues to be a disease threat to Atlantic salmon aquaculture in Ireland, and as such, it is of growing importance to understand how the virus spreads. Genetic sequences allow for transmission pathways to be examined, with whole genomes providing the most accurate information. In this study, whole genome sequencing has been applied to Irish strains of PMCV, in doing so revealing how > 80% of the genetic diversity of the virus lies outside the commonly sequenced open reading frames (ORFs). Second, this paper examines the effectiveness of incorporating a MinION sequencing approach into routine diagnostics by comparing a MinION generated genome to the corresponding sequence generated via Illumina MiSeq. The results showed the MinION genome shared 99.59% identity with the Illumina genome, and while this accuracy may be sufficient for studies such as pathogen identification and deeper evolutionary questions, it was shown to be insufficient for accurately tracking viral transmission pathways. Finally, comparing Irish and Faroese sequences reveals that some strains of PMCV in Ireland may originate from wild fish.

Continuous nitrite and nitrate monitoring of recirculating aquaculture systems using a deployable ion chromatography-based analyser - Meritxell Grau Butinyac; Valeria Arenas Montaño; Jamie Downes; Neil M. Ruane; Elizabeth Ryder; Fintan Egan; Thomas Staessen; Brett Paull; Eoin Murray (Aquaculture International, 2024)

Assessment of gill microbiome of two strains of Atlantic salmon reared in flowthrough and recirculation hatcheries and following seawater transfer - Petra R. Quezada-Rodriguez; Jamie Downes; Fintan Egan; Richard S. Taylor; Samantha White; Aisling Brenan; Megan L. Rigby; Barbara F. Nowak; James W. Wynne; Neil M. Ruane (Aquaculture, 2024)

Planning and licensing for marine aquaculture - Lynne Falconer; Karl Cutajar; Amalia Krupandan; Elisa Capuzzo; Richard A. Corner; Tim Ellis; Keith Jeffery; Eirik Mikkelsen; Heather Moore; Francis X. O'Beirn; Pauline O'Donohoe; Neil M. Ruane; et al. (Reviews in Aquaculture, 2023)
Marine aquaculture has the potential to increase its contribution to the global food system and provide valuable ecosystem services, but appropriate planning, licensing and regulation systems must be in place to enable sustainable development. At present, approaches vary considerably throughout the world, and several national and regional investigations have highlighted the need for reforms if marine aquaculture is to fulfil its potential. This article aims to map and evaluate the challenges of planning and licensing for growth of sustainable marine aquaculture. Despite the range of species, production systems and circumstances, this study found a number of common themes in the literature; complicated and fragmented approaches to planning and licensing, property rights and the licence to operate, competition for space and marine spatial planning, emerging species and diversifying marine aquaculture production (seaweed production, Integrated Multi‐Trophic Aquaculture [IMTA], nutrient and carbon offsetting with aquaculture, offshore aquaculture and co‐location and multiuse platforms), and the need to address knowledge gaps and use of decision‐support tools. Planning and licensing can be highly complicated, so the UK is used as a case study to show more detailed examples that highlight the range of challenges and uncertainty that industry, regulators and policymakers face across interacting jurisdictions. There are many complexities, but this study shows that many countries have undergone, or are undergoing, similar challenges, suggesting that lessons can be learned by sharing knowledge and experiences, even across different species and production systems, rather than having a more insular focus.

Prevalence of epitheliocystis in freshwater Atlantic salmon reared in flow‐through and recirculation aquaculture systems - Petra R. Quezada‐Rodriguez; Richard S. Taylor; Jamie Downes; Fintan Egan; Samantha White; Aisling Brenan; Megan Rigby; Barbara F. Nowak; Neil M. Ruane; James W. Wynne (Journal of Fish Diseases, 2022)
Epitheliocystis, an intracellular bacterial infection in the gills and skin epithelium, has been frequently reported in Atlantic salmon ( Salmo salar ) during freshwater production in a number of countries. This study describes the prevalence and intensity of a natural epitheliocystis infection present in the gills of two strains of Atlantic salmon reared in either a flow‐through (FT) or a recirculation aquaculture system (RAS) in Ireland. Repeated sampling of gills prior to and throughout seawater transfer, histology and quantitative real‐time PCR were used to determine infection prevalence and intensity. Despite no clinical gill disease, and minor histopathological changes, epitheliocystis lesions were identified in histology at all time points. Specific PCR confirmed the presence of Candidatus Clavichlamydia salmonicola in both strains and its number of copies was correlated with intensity of epitheliocystis lesions. A significant interaction between hatchery system and fish strain on the prevalence and intensity of gill epitheliocystis was found both using histological and molecular methods. Specifically, fish from FT had higher prevalence and intensity than RAS reared fish and within FT, the Irish cohort were more affected than Icelandic.

Experimental infection trials with European North Atlantic ranavirus ( Iridoviridae ) isolated from lumpfish ( Cyclopterus lumpus , L.) - Felix Scholz; Niccolò Vendramin; Niels Jørgen Olesen; Argelia Cuenca; Tine Moesgaard Iburg; Luca Mirimin; Ian O'Connor; Neil M. Ruane; Hamish D. Rodger; Eugene MacCarthy (Journal of Fish Diseases, 2022)
European North Atlantic ranavirus (ENARV, Iridoviridae ), is a ranavirus species recently isolated from lumpfish ( Cyclopterus lumpus , L.), which are used as cleaner fish in Atlantic salmon ( Salmo salar ) farming in Northern Europe. This study aimed to investigate (1) the virulence of ENARV isolates from Ireland, Iceland and the Faroe Islands to lumpfish; (2) horizontal transmission between lumpfish; and (3) virulence to Atlantic salmon parr. Lumpfish were challenged in a cohabitation model using intraperitoneally (IP) injected shedders, and naïve cohabitants. IP challenge with isolates from Iceland (1.9 × 10 7 TCID 50 ml −1 ) and the Faroe Islands (5.9 × 10 7 TCID 50 ml −1 ) reduced survival in lumpfish, associated with consistent pathological changes. IP challenge with the Irish strain (8.6 × 10 5 TCID 50 ml −1 ) did not significantly reduce survival in lumpfish, but the lower challenge titre complicated interpretation. Horizontal transmission occurred in all strains tested, but no clinical impact was demonstrated in cohabitants. Salmon parr were challenged by IP injection with the Irish isolate, no virulence or virus replication were demonstrated. A ranavirus qPCR assay, previously validated for fish ranaviruses, was first used to detect ENARV in tissues of both in lumpfish and Atlantic salmon. This study provides the first data on the assessment of virulence of ENARV isolates to lumpfish and salmon, guidelines for the diagnosis of ENARV infection, and poses a basis for further investigations into virulence markers.

Presence and genetic variability of Piscine orthoreovirus genotype 1 (PRV‐1) in wild salmonids in Northern Europe and North Atlantic Ocean - Niccoló Vendramin; Argelia Cuenca; Juliane Sørensen; Anna L. F. Alencar; Debes H. Christiansen; Jan A. Jacobsen; Charlotte Axen; François Lieffrig; Neil M. Ruane; Patrick Martin; Timothy Sheehan; Tine M. Iburg; et al. (Journal of Fish Diseases, 2019)
Piscine orthoreovirus genotype 1 (PRV‐1) is widespread in farmed Atlantic salmon ( Salmo salar L.) populations in northern Europe, Canada and Chile. PRV‐1 occurs in wild fish in Norway and Canada; however, little information of its geographical distribution in wild populations is currently available, and the effect of PRV‐1 infection in wild populations is currently unknown. In this study, we present the findings of a survey conducted on 1,130 wild salmonids sampled in Denmark, Sweden, Ireland, Faroe Islands, France, Belgium and Greenland between 2008 and 2017. PRV‐1 is reported for the first time in wild salmonids in Denmark, Sweden, Faroe Island and Ireland. The annual PRV‐1 prevalence ranged from 0% in France, Belgium and Greenland to 43% in Faroe Islands. In total, 66 samples tested positive for PRV‐1, including Atlantic salmon broodfish returning to spawn and Atlantic salmon collected at the feeding ground north of Faroe Islands. The phylogenetic analysis of S1 sequences of the PRV‐1 isolates obtained in this survey did not show systematic geographical distribution. This study sheds light on the spread and genetic diversity of the virus identified in populations of free‐living fish and provides rationale for screening wild broodfish used in restocking programmes.

Genetic diversity of piscine myocarditis virus in Atlantic salmon Salmo salar L. in Ireland - Andrew J. Tighe; Jens Carlsson; Teresa Morrissey; Fiona Swords; Neil M. Ruane (Journal of Fish Diseases, 2019)
Piscine myocarditis virus (PMCV) is a double‐stranded RNA virus which has been linked to cardiomyopathy syndrome (CMS) in Atlantic salmon ( Salmo salar L.). The first recorded outbreak of CMS in Ireland occurred in 2012. Heart tissue samples were collected in the current study from farmed Atlantic salmon from various marine sites around Ireland, and the open reading frames (ORFs) 1 and 3 were amplified and sequenced in order to examine the genetic diversity of PMCV. Results showed PMCV to be largely homogenous in Irish samples, showing little genetic diversity. However, several amino acid positions within both ORF1 and ORF3 showed consistent variations unique to the Irish PMCV strains when compared with previously published Norwegian strains. The phylogeny generated in the present study suggests that PMCV may have been introduced into Ireland in two waves, both coming from the southern part of PMCV's range in Norway. In addition, over three‐quarters of the PMCV strains which were sequenced came from fish not exhibiting any clinical signs of CMS, suggesting that either PMCV is evolving to become less virulent in Ireland or Irish Atlantic salmon are developing immunity to the disease.

Isolation of salmonid alphavirus subtype 6 from wild‐caught ballan wrasse, Labrus bergylta (Ascanius) - Neil M. Ruane; David Swords; Teresa Morrissey; Michelle Geary; Cathy Hickey; Evelyn M. Collins; Fiona Geoghegan; Fiona Swords (Journal of Fish Diseases, 2018)
The use of cleaner fish as a biological control for sea lice in Atlantic salmon aquaculture has increased in recent years. Wild‐caught wrasse are commonly used as cleaner fish in Europe. In Ireland, samples of wrasse from each fishing area are screened for potential pathogens prior to their deployment into sea cages. Salmonid alphavirus was isolated from a pooled sample of ballan wrasse, showing no signs of disease, caught from the NW of Ireland. Partial sequencing of the E2 and nsP3 genes showed that it was closely related to the previously reported SAV subtype 6. This represents only the second isolation of this subtype and the first from a wild fish species, namely ballan wrasse.

Evaluation of Non-destructive Molecular Diagnostics for the Detection of Neoparamoeba perurans - Jamie K. Downes; Megan L. Rigby; Richard S. Taylor; Ben T. Maynard; Eugene MacCarthy; Ian O'Connor; Mar Marcos-Lopez; Hamish D. Rodger; Evelyn Collins; Neil M. Ruane; Mathew T. Cook (Frontiers in Marine Science, 2017)

Phylogenetic analysis of infectious pancreatic necrosis virus in Ireland reveals the spread of a virulent genogroup 5 subtype previously associated with imports - Neil Martin Ruane; Stephen John McCleary; Lorraine Julie McCarthy; Kathleen Henshilwood (Archives of Virology, 2015)

Health of farmed fish: its relation to fish welfare and its utility as welfare indicator - Helmut Segner; Henrik Sundh; Kurt Buchmann; Jessica Douxfils; Kristina Snuttan Sundell; Cédric Mathieu; Neil Ruane; Fredrik Jutfelt; Hilde Toften; Lloyd Vaughan (Fish Physiology and Biochemistry, 2012)